Stand-off Spectroscopies Under Controlled Atmospheric and Temperature Planetary Conditions Using a Multipurpose Thermal Vacuum Chamber - Lucena Navarro, Patricia; Moros-Portolés, Javier; García-Gómez, Laura; Delgado-Pérez, Tomás; Cabalín-Robles, Luisa María; Fortes-Román, Francisco Javier; Vadillo-Pérez, José Miguel (My University, 2026)
The availability of thermal vacuum chambers (TVAC) represents a need in today´s planetary research. A TVAC must be capable of operate under representative conditions (temperature, gas composition, pressure, radiation flux …) of space exploration targets but also have a useful volume compatible with the performing experiments and the testing of equipment under mimicked scenarios. This abstract detail the TVAC designed and installed at UMALASERLAB to serve the astrochemical community. With a length of 12 meters and a useful internal diameter of 1.6 meters, the chamber operates in a temperature range between 200 K - 400 K and can be oil-free pumped down from atmospheric pressure to 10-4 mbar in the current configuration. Additional upgrades may extend the pressure range up to the 10-6 mbar range. Such figures and dimensions turn the TVAC of UMALASERLAB a powerful and versatile tool for space-related studies in chemistry, biology and engineering. The internal surface of the TVAC is black painted with a special enamel to improve the thermal emission of the surface itself and maximize light absorption (> 95 % at any angle) to reduce flares and ghost effects in the recorded spectra. For experiments demanding deep UV illumination, a high-power Xe lamp provides illumination conditions similar to those at Mars surface in the UV-A, UV-B and UV-C spectral regions over a diameter of 50 cm in the geometrical center of the TVC. A graphic user interface allows local and remote visualization, control and data logging of the vacuum pumps, the cooling/heating system, the pressure gauges, the thermocouple gauges, and the mass flow controllers for gas mix load in the chamber. Different experiments performed inside the TVAC will be described including laser-induced breakdown spectrometry (LIBS), laser-induced plasma acoustic (LIPAC) and thermal imaging monitoring.
Keywords: Espectroscopia - Congresos; Planetary spectroscopy; Stand-off spectroscopies; Thermal Vacuum Chamber